25
$\begingroup$

How can I formally prove that the sum of two independent binomial variables X and Y with same parameter p is also a binomial ?

$\endgroup$
  • 1
    $\begingroup$ why was that question down voted? $\endgroup$ – bubakazouba Oct 25 '15 at 3:49
27
$\begingroup$

Let $(B_k)_k$ be a sequence of iid Bernoulli distributed random variable with $P(B_k=1)=p$ for $k=1,2,\dots$

Then $$X:=B_1+\cdots+B_n$$ is binomially distributed with parameters $n,p$ and $$Y:=B_{n+1}+\cdots+B_{n+m}$$ is binomially distributed with parameters $m,p$. It is evident that $X$ and $Y$ are independent.

Now realize that $$X+Y=B_1+\cdots+B_{n+m}$$ is binomially distributed with parameters $n+m,p$.

This spares you any computations.

$\endgroup$
  • 1
    $\begingroup$ Thanks for your answer. Can you explain in some more details how did you get to your first result ? $\endgroup$ – Piyush Maheshwari Mar 9 '15 at 20:54
  • 1
    $\begingroup$ If $X$ has binomial distribution with parameters $n,p$ then it can be identified as the number of "successes" by having $n$ independent experiments all having a probability of $p$ to succeed. Set $B_i=1$ if experiment $i$ succeeds and $B_i=0$ otherwise. This for $i=1,\dots,n$. Then the number of successes (that is $X$) equals $B_1+\cdots +B_n$. $\endgroup$ – drhab Mar 10 '15 at 9:44
  • $\begingroup$ Oh sorry I misread the term Bernouilli as Binomial. Thank you so much, this is very easy to reason about. $\endgroup$ – Piyush Maheshwari Mar 10 '15 at 17:35
19
$\begingroup$

Just compute. Suppose $X \sim \def\Bin{\mathord{\rm Bin}}\Bin(n,p)$, $Y \sim \Bin(m,p)$. Now let $0 \le k \le n+m$, then \begin{align*} \def\P{\mathbb P}\P(X+Y = k) &= \sum_{i=0}^k \P(X = i, Y = k-i)\\ &= \sum_{i=0}^k \P(X=i)\P(Y=k-i) & \text{by independence}\\ &= \sum_{i=0}^k \binom ni p^i (1-p)^{n-i} \binom m{k-i} p^{k-i} (1-p)^{m-k+i}\\ &= p^k(1-p)^{n+m-k}\sum_{i=0}^k \binom ni \binom m{k-i} \\ &= \binom {n+m}k p^k (1-p)^{n+m-k} \end{align*} Hence $X+Y \sim \Bin(n+m,p)$.

$\endgroup$
  • $\begingroup$ Thanks for your answer. Can you please explain how is $ \sum_{i=0}^k \binom ni \binom m{k-i} $ equal to $ \binom {n+m}{k} $ ? $\endgroup$ – Piyush Maheshwari Mar 5 '15 at 19:33
  • 3
    $\begingroup$ @Piyush see Vandermonde's identity $\endgroup$ – polpetti Jan 3 '17 at 20:13
7
$\begingroup$

Another way: Suppose $X\sim$ Bin$(n, p)$ and $Y\sim$ Bin$(m, p)$. The characteristic function of $X$ is then $$\varphi_X(t) = E[e^{itX}]=\sum_{k=0}^ne^{itk}{n\choose k}p^k(1-p)^{n-k}=\sum_{k=0}^n{n\choose k} (pe^{it})^k(1-p)^{n-k}=(1-p+pe^{it})^n.$$

Since $X, Y$ independent, $$\varphi_{X+Y}(t)=\varphi_{X}(t)\varphi_Y(t)=(1-p+pe^{it})^n(1-p+pe^{it})^m=(1-p+pe^{it})^{n+m}.$$

By uniqueness, we get $X+Y\sim$ Bin$(n+m, p)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.